Answer:
(2,0)
Explanation:
Given:
The equation is given as:
![y=-3x^(2)+5x+2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/bmh6z3oopq4oodqm7npxucgcln3ptl2hop.png)
For x intercept,
.
Therefore,
![-3x^(2)+5x+2=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/5sx9x28dfgnt0bk3prmw9t9ay1xcu9z5r3.png)
Now, comparing this with the standard quadratic equation
, we get
![a=-3,b=5,c=2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/irddcx53jg4i1txg1z6ctgfh26ipakgvro.png)
Now, using quadratic formula for the above equation,
![x=\frac{-b \pm \sqrt{b^(2)-4ac}}{2a}\\x=\frac{-5 \pm \sqrt{5^(2)-4(-3)(2)}}{2(-3)}\\x=(-5 \pm √(25+29))/(-6)\\x=(-5 \pm √(49))/(-6)\\x=(-5 \pm 7)/(-6)\\x=(-5-7)/(-6)\textrm{ or }x=(-5+7)/(-6)\\x=(-12)/(-6)\textrm{ or }x=(2)/(-6)\\x=2\textrm{ or }x=-(1)/(3)=-0.33](https://img.qammunity.org/2020/formulas/mathematics/middle-school/a9wrk8281jwk3si3scdjyqf3ny2y7jvyxb.png)
Therefore, there are two x intercepts. One was given as (-0.33,0). So, the other one is (2, 0).